Temperature-responsive bending of a bilayer gel. (15th March 2015) - Morimoto, Takuya; Ashida, Fumihiro
Abstract: We investigate the finite bending of a bilayer gel in response to temperature under plane strain condition. We demonstrate that our model based on finite elasticity predicts larger bending curvatures of the bilayers compared with the linear model based on the elementary beam theory, and a high swelling ratio in the bilayer enhances the differences between both models. We also show that the folding shape of the bilayer can be controlled by tuning the ratio of shear modulus and the length-to-height ratio and that multiple neutral axes can exist in the bilayer under certain conditions. Our results could provide the basis for further numerical modeling of a layered gel as well as a spatially patterned gel to create 3D complex self-folding structures.